PENGUATAN KEDUDUKAN PRANATA HAK SERVITUT DAN HUKUM BERTETANGGA DALAM YURISPRUDENSI - Rizal Sofyan Gueci (Universitas Pamulang, 2016)
The Constitution has laid the foundation of checks and balances amongst the main state organs namely the executive, the legislative and the judicial power. This order as a guideline in the state and society, till the Village level and within groups in the village such as the Neighborhood and citizen groups. Servitut Rights and neighbors law answer challenges of development of human settlements sustainably and resilient. Servitut rights as a property rights regulated in Neighbor law book II Indonsian Civil Code of 1848 or in adat law term called easement (hak melalui tanah orang lain) which known by adat community entity is not older than the easement is recognized by customary law in almost adat law community entity throughout the territory of Indonesia. The servitut right is the easement of yard (erfdiensbaarheid) or burden to rest on the grounds that one for the benefit of the another yard such that the owner of the yard were crushed should let the owner of the yard oppressor to pass through, drain the water (clear) on it, take view out through the window etc. This devotion land does not end with the death or replacement of yard owners concerned (Article 674 of the Indon. Civil Code). There are still remnants of feudalism and colonialism in tribal society, reflecting the concrete cases in the community there is disturbance against the rights of servitut with vigilante, then the rule of law invoked repeatedly and generating permanent jurisprudence. Kedudukannya hak servitut tidak tergoyahkan dengan adanya UUPA 1960 yang mengatakan semua hak atas tanah mempunyai fungsi sosial dan hukum adat dijadikan dasar dari hukum agraria nasional. The position of Servitut rights is impregnable with the Basic Agrarian Law 1960 (BAL) that says all rights on land has social functions and customary law form the basis of the national agrarian law. In Article I point 6 of BAL No. 5 year 1960 proves Indonesia is in a row of civilized countries that accommodates this legal institution. Jurisprudence confirm customary law as a living law as well as the Civil Code 1848 according to Supreme Court Circuler of 1963 treat as unwritten customary law in order to prevent the legal vacuum and reaching the objectives of the law. Jurisprudence has been recognized as one of the legitimate source of law in the Republic of Indonesia. Indonesian Judges have shown its class in the world of justice, who did not want to look different in servitut rights issues which is an universal phenomenon. Almost all civilized countries of the UN members have recognized the existence of this institute servitut rights, both in the Code book as well as in its jurisprudence. Servitut rights institution is rooted in the common law ius commune since Roman Empire, which can not be ignored, despite overall individualistic Roman law, but in particular there are elements of social function. Servitut (lat.) is accommodated into the book of the law in almost all countries in the world, through colonialize, import law, voluntary transplants in the law of one self. Boedi Harsono, as nationalist and socialist thinker and R. Supomo as father of Indonesian customary law and by youth in 1928 is regarded as a national law with the smooth call it